VENTILATOR ASSOCIATED PNEUMONIA - Wiryana, Made (journal of internal medicine, 2012)
Ventilator Associated Pneumonia (VAP) is defined as nosocomial pneumonia that occurred 48 hours after the patient had a mechanical ventilation support either from endotracheal tube or tracheostomy tube. VAP ussually charactherized by 3 component sign of systemic infection: fever, tachycardia and leukocytosis followed by new infiltrate sign or a worsening scheme on the chest x ray and bacteriologic findings of the causal of lung infection, but acctually we can diagnosed a VAP based on the findings of a number of criteria: histopathologic examination of the lung tissue from an open biopsy, a fast cavity formation of a lung infiltrate without any sign of tuberculosis or malignancy and a positive pleural fluid culture, in which the species that found on the blood culture and airway were the same. The insidens of VAP are high, according to the foreign literature approximately between 9 – 27 % from all Intensive Care Unit population. This condition made VAP as the first causal of a nosocomial infection in the Intensive Care Unit. The mortality rate of VAP is also high, Chastre and Fagon stated that the crude mortality rate can reach of 76%. Early onset VAP which occurred on the first 4th day after admission in the Intensive Care Unit ussually had a better prognosis because of caused by a still antibiotic sensitive pathogens. The Late onset VAP which occurred after 5 days or more after hospitalization, has worse prognosis because of caused by a multidrug resistance (MDR) pathogens. In order to define the pathogens that caused VAP, some scientist made a classification of VAP patient based on the degree of disease, risk factor and the onset, which is the group I with mild-moderate degree, common risk factor and the onset is anytime during hospitalization or a severe degree with an early onset, ussually caused by a gram negative bacteria. The group II, patient with a mild-moderate degree, specific risk factor that happened anytime during hospitalization, ussually caused by all bacteria in the group I added with an anaerob bacteria. The group III, patient with a severe degree, early onset with specific risk factor or a late onset, ussually caused by Pseudomonas aeruginosa, Acinetobacter sp and MRSA. Other approach is by classifying the bacteria causing VAP in a primary endogen, secondary and eksogen type. Prevention of VAP can be done by 2 different ways, first by a non pharmachologic way, routine and standard things that ussually done in the ICU, but this action still could not enough in lowering the insidens of VAP. Second, by a pharmachologic way, Selective Decontamination of the Digestive Tract (SSD) and Oropharyngeal Decontamitation (OD). SSD is proven effective empirically in preventing VAP but the used of antimicrobial can caused a higher risk on resistention. SDD is not recommended as a routine action in preventing VAP so that OD with the used of antiseptic is preferred as another alternative.
Keywords: Ventilator associated pneumonia, mechanical ventilation, critically ill patients